Surgical therapy, incidence of recurrence after limbal autograft transplantation and surgical technique without transplantation - Cheleva Markovska, Vesna; Antova M.; Djajkovska E. (Ophthalmological Society of Northen Greece, 2002)
Aim: To evaluate the success rates of surgical techniques for primary pterigium: pterigium excision with limbal autograft transplantation and pterigium excision with complete suture of conjunctiva without transplantation Methods: 75 cases with primary pterigium was prospectively reviewed. Outcome was evaluated in terms of recurrence of pterigia onto the cornea .The patients were divided into two groups.4 0 eyes were operated by limbal autograft transplantation (20 cases by pterigium encroaches the cornea 3mm and 20 cases by pterigium encroaches the cornea 3mm and more ). 35 cases were operated by pterigium excision with complete suture of conjunctiva without transplantation 20 cases by pterigium encroaches the cornea 3mm and 15 cases by pterygium encroaches the cornea 3mm and more). Results: Mean follow up was 12 months (2-24 months). 4 out of 40 recurred (10%) after the limbal autograft transplantation, while 14 of 35 cases recurred (40%) after the pterigium excision with complete suture of conjunctiva without transplantation. One surgeon performed the surgery. Conclusion: Conjunctiva-limbus autografts in pterigia have excellent efficacy against within the first year.